Knowledge, Attitude, Practice, and Status of Infection Control among Iranian Dentists and Dental Students: A Systematic Review - Behnam Moradi Khanghahi; Zahra Jamali; Fatemeh Pournaghi Azar; Mohammad Naghavi Behzad; Saber Azami-Aghdash (Tabriz University of Medical Sciences, 2013)
Background and aims. Infection control is an important issue in dentistry, and the dentists are primarily responsible for observing the relevant procedures. Therefore, the present study evaluated knowledge, attitude, practice, and status of infection control among Iranian dentists through systematic review of published results. Materials and methods. In this systematic review, the required data was collected searching for keywords including infection, infection control, behavior, performance, practice, attitude, knowledge, dent*, prevention, Iran* and their Persian equivalents in PubMed, Science Direct, Iranmedex, SID, Medlib, and Magiran databases with a time limit of 1985 to 2012. Out of 698 articles, 15 completely related articles were finally considered and the rest were excluded due to lake of relevance to the study goals. The required data were extracted and summarized in an Extraction Table and were analyzed manually. Results. Evaluating the results of studies indicated inappropriate knowledge, attitude, and practice regarding infection control among Iranian dentists and dental students. Using personal protection devices and observing measures required for infection control were not in accordance with global standards. Conclusion. The knowledge, attitudes, and practice of infection control in Iranian dental settings were found to be inadequate. Therefore, dentists should be educated more on the subject and special programs should be in place to monitor the dental settings for observing infection control standards.